Carbon‐Dot‐Based Two‐Photon Visible Nanocarriers for Safe and Highly Efficient Delivery of siRNA and DNA. Issue 8 (2nd April 2014) - Wang, Liqin; Wang, Xiaoyong; Bhirde, Ashwinkumar; Cao, Jianbo; Zeng, Yun; Huang, Xinglu; Sun, Yaping; Liu, Gang; Chen, Xiaoyuan
<x xml:space="preserve">Abstract</x> A simple and versatile nanoparticulate siRNA and DNA delivery vehicle is reported, based on photonic Cdots by using Alkyl–PEI2k for surface passivation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>